Mobile team performance in integrated palliative care for patients with HIV infection - D. A. Gusev; O. N. Leonova; S. D. Dugin; N. L. Smirnova; A. S. Shelomov (Журнал инфектологии, 2020)
The article presents the experience of the mobile team as an integral component of palliative care for patients with HIV infection.Objective: To analyze the effectiveness of the mobile team as a key component of palliative care for patients with advanced stages of  HIV infection and comorbid conditions.Materials and methods: In 2018, a joint project of the St. Petersburg AIDS Center and the BF (charity foundation) «Humanitarian Action» created a mobile team to provide  onsite medical and social assistance to patients with HIV  infection. The article presents the results of the project for 2018–2019. We studied the composition of patients, their needs for various types of support, as well as assessing the problems in providing this type of service to patients with HIV infection.  The analysis of the work of the mobile team for 2018–2019. The composition of patients in need of medical and social assistance was studied. Results. In the supervision of the mobile team were 79 patients with HIV. The main tasks of the mobile team were to identify patients with HIV infection who suffered from severe opportunistic diseases, for various reasons they could not come to the doctor’s center for antiretroviral therapy, and also monitor the effectiveness of treatment and psychological support for sedentary and hard-to-reach groups of patients.Conclusion: Given the increase in the number of patients with advanced HIV infection and comorbid conditions, the creation of mobile teams that are part of palliative care is an essential part of comprehensive medical and social care.